Blastomyces dermatitidis: Antibody Detection in Sera from Dogs with Blastomycosis with Yeast Lysate Antigens Produced from Human and Dog Isolates - Katie Mondada; Jessie Fullmer; Eric Hungerford; Katrina Novack; Kristen Vickers; Gene Scalarone (Veterinary Medicine International, 2014)
Dogs are common hosts to the fungal organism Blastomyces dermatitidis, which causes the systemic disease blastomycosis. The goal of our study was to compare the reactivity of two B. dermatitidis yeast lysate antigens prepared from dog isolates (ERC-2, Wisconsin; T-58, Tennessee) and two lysate antigens prepared from human isolates (B5931 and B5896, Minnesota) against 48 serum specimens from dogs with confirmed blastomycosis using the indirect enzyme-linked immunosorbent assay (ELISA). Secondarily, we used three different ELISA substrates (Ultra TMB: A, SureBlue: B, and SureBlue Reserve: C) to compare the effectiveness of each substrate. Mean absorbance values ranged from 0.446 (B) to 0.651 (C) for the B5931 antigen and from 0.393 (B) to 0.540 (C) for the ERC-2 antigen in Trial 1. In Trial 2, the absorbance values ranged from 0.628 (B) to 0.909 (A) for the B5896 antigen and from 0.828 (B) to 1.375 (C) for the T-58 antigen. In Trial 1, the lysate antigen prepared from the human isolate B5931 exhibited the highest absorbance value and in Trial 2 the lysate prepared from the dog isolate T-58 was the most reactive. The overall results thus indicated that the T-58 lysate was the optimal reagent when used to detect antibody with the Sure-Blue Reserve substrate. Our laboratory is continuing to study B. dermatitidis antigen and substrate combinations for the reliable immunodiagnosis of blastomycosis in humans and animals.